Incidence of Sudden Unexpected Postnatal Collapse in the Therapeutic Hypothermia Era - Filippi, Luca; Laudani, Emanuela; Tubili, Flavia; Calvani, Maura; Bartolini, Isabella; Donzelli, Gianpaolo (American Journal of Perinatology, 2017)
Objective Hypothermia is considered the treatment of choice for newborns with hypoxic-ischemic encephalopathy. Even though currently no consensus exists regarding the opportunity to extend this treatment also to newborns with sudden unexpected postnatal collapse (SUPC), this treatment is frequently adopted. The aim of the study was to evaluate whether the availability of hypothermia also for collapsed newborns in a tertiary level center may impact the estimated incidence of SUPC.Study Design A retrospective study was performed comparing the number of newborns admitted with the diagnosis of SUPC in the tertiary referral Neonatal intensive care unit of Florence in the period before (2008–2010) and after (2011–2014) the introduction of hypothermia treatment for newborns with SUPC.Result After introducing active cooling also to newborns with SUPC, the number of newborns with SUPC admitted to our center augmented and, consequently, SUPC incidence apparently increased from 5.3 to 15.5/100,000 live births, even though this difference did not reach statistical significance (odds ratio = 0.340; 95% confidence interval = 0.071–1.639; p = 0.179).Conclusion The apparent increase of SUPC incidence is probably related to a more effective centralization of newborns in our referral center but suggests that the real incidence of SUPC is probably significantly higher than currently estimated.
Keywords: therapeutic hypothermia; SUPC; hypoxic-ischemic encephalopathy; newborn